The Role of German Words in the English language (Journal of human and social sciences, 2026)
This paper aims to throw light on some of the most important borrowing in English language, that is from German language. The German words are used in day today life and all the time. Anyone having little idea of these borrowing will easily understand both the languages. The focus here is on the history of German language and how British old English was used in German Language. Several researchers have proved the fact that vocabulary plays the central role in teaching language. English as a foreign language is not an exception to it as a learn to devote much efforts and time to understand and enhance and use the vocabulary. The various technique is used to help language learner tackle the different in learning everything in a language. To understand language and its etymology better one has to have a general idea of the history of the language. The history of English language generally began with German invasion Britain in the 5th century AD The English language has seen three area of development old 450-1150, ..middle 1150 to 1500 and early modern English 1500-18. Late modern English after 1800.The old English was spoken by German tribes which had much different from the current language but it had half of the vocabulary from the d English roots be strong water up to 1100. Greek words started in practice in 600 AD in 400 AD Latin words started adding to English. And a William Conquered Duke French word was used by the upper elite class during Chaucer time. These borrowing of German, French and Greek became part of English and around 10,000 words of French made inroad in the English language. The sun never set on the British empire as the adopted many foreign words including Sanskrit, Hindi& Urdu coming up and integrating into the main language from different countries this led to an emergence of difference between commonwealth, British and American English. Which is now spoken by more than billion around the world now or more.
Keywords: Linguistic Borrowing; Germanic Influence; Vocabulary Development; Linguistic History; English Dialectal Variation